2023
DOI: 10.1186/s42836-023-00172-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pain after total hip arthroplasty: a systematic review

Abstract: Background Approximately 23% of patients develop hip pain after total hip arthroplasty (THA). In this systematic review, we aimed to identify risk factors associated with postoperative pain after THA to optimize preoperative surgical planning. Methods Six literature databases were searched for articles published from January 1995 to August 2020. Controlled trials and observational studies that reported measurements of postoperative pain with assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Similar results were found for preoperative BMI, with no statistically significant difference in pain following rTSA across varying BMIs as well as patient sex. The lack of association with BMI seems to reflect previous studies, which have shown improvements in pain are similar among patients following arthroplasty procedures across a variety of joints regardless of BMI, including total knee arthroplasty [48] as well as hip arthroplasty [9]. These preoperative factors showing little association with postoperative pain provide further evidence for rTSA being an efficacious intervention for a wide spectrum of patient demographics.…”
Section: Discussionmentioning
confidence: 69%
“…Similar results were found for preoperative BMI, with no statistically significant difference in pain following rTSA across varying BMIs as well as patient sex. The lack of association with BMI seems to reflect previous studies, which have shown improvements in pain are similar among patients following arthroplasty procedures across a variety of joints regardless of BMI, including total knee arthroplasty [48] as well as hip arthroplasty [9]. These preoperative factors showing little association with postoperative pain provide further evidence for rTSA being an efficacious intervention for a wide spectrum of patient demographics.…”
Section: Discussionmentioning
confidence: 69%
“…Many patients suffer from obvious pain after hip arthroplasty and increasing interest is focused on its perioperative analgesia in order to promote early postoperative mobilization and discharge. [ 1 3 ] Perioperative pain control is of utmost importance for patients’ recovery and satisfaction. [ 4 , 5 ] Perioperative analgesia is able to reduce opioid consumption, improve immediate postoperative function, and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…While THA is generally a highly successful procedure, there remains significant variability in postoperative pain recovery. 1 Studies indicate that about 23% of patients may encounter postoperative hip pain, 2 - 5 with a subset even reporting stagnation or exacerbation of pain following the procedure. 4 While loosening of implants, infections, periprosthetic fractures, and soft-tissue abnormalities are recognized causes of postoperative pain, 3 numerous instances lack a clear correlation with radiological or mechanical irregularities.…”
Section: Introductionmentioning
confidence: 99%
“… 4 While loosening of implants, infections, periprosthetic fractures, and soft-tissue abnormalities are recognized causes of postoperative pain, 3 numerous instances lack a clear correlation with radiological or mechanical irregularities. 1 …”
Section: Introductionmentioning
confidence: 99%